A hero ain't nothin' but a sandwich - Childress, Alice (New York, N.Y. : Avon Books, 1973)
The life of a thirteen-year-old Harlem youth on his way to becoming a confirmed heroin addict is seen from his viewpoint and from that of several people around him.
Reprint. Originally published: New York : Coward, McCann & Geoghegan, 1973.
Keywords: Drug abuse -- Fiction; African Americans -- Social conditions -- Fiction